Hedging performance of futures contracts: The case of FTSE BMKLCI futures and the CPO futures contracts in Malaysia - Islam, Mohd Aminul; Pah, Chin Hee (2018)
This study aims to investigate the hedging performance of two derivative instruments traded in Bursa Malaysia Derivative Exchange. They are Kuala Lumpur composite index (KLCI) futures contracts and the crude palm oil (CPO) futures contracts covering the period from January 4, 2010 to October 31, 2016. Four different competing econometric models comprising of the conventional ordinary least squares (OLS) model, vector autoregression (VAR) model, vector error correction mechanism (VECM) and the multivariate generalized autoregressive conditional heteroscedasticity (MGARCH) models are employed to estimate and measure optimal hedge ratios and their hedging performances. The empirical results show that the MGARCH model performs better in the reduction of risk for the case of CPO futures contracts, while VECM performs better in managing equity risk for the case of KLCI futures contracts. In both cases, more than 70% of the risks are found eliminated which indicate a good level of hedging effectiveness of the two derivative instruments. However, CPO futures contracts perform slightly better than the KLCI futures contracts. This suggests that the potential traders and the investors can use these two derivative products as effective instruments in managing the risk that may arise due to unfavorable movement in the market prices. Both VECM and MGARCH models can be used efficient models in designing hedging strategy.